RETRACTED: Use of paraboloid solar concentrators to reduce heat consumption of residential buildings in the climatic conditions of Uzbekistan - Kamolov J.J.; Mirzayev M.S.; Fayziyev Sh.Sh.; Samiev K.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001